Vaccine induced memory CD8+ T cells efficiently prevent viral transmission from the respiratory tract - Zhou, Jinglin; Uddback, Ida; Kohlmeier, Jacob E.; Christensen, Jan Pravsgaard; Thomsen, Allan Randrup (Frontiers in Immunology, 2023)
Introduction: Mucosal immunization eliciting local T-cell memory has been suggested for improved protection against respiratory infections caused by viral variants evading pre-existing antibodies. However, it remains unclear whether T-cell targeted vaccines suffice for prevention of viral transmission and to which extent local immunity is important in this context. Methods: To study the impact of T-cell vaccination on the course of viral respiratory infection and in particular the capacity to inhibit viral transmission, we used a mouse model involving natural murine parainfluenza infection with a luciferase encoding virus and an adenovirus based nucleoprotein targeting vaccine. Results and discussion: Prior intranasal immunization inducing strong mucosal CD8+ T cell immunity provided an almost immediate shut-down of the incipient infection and completely inhibited contact based viral spreading. If this first line of defense did not operate, as in parentally immunized mice, recirculating T cells participated in accelerated viral control that reduced the intensity of inter-individual transmission. These observations underscore the importance of pursuing the development of mucosal T-cell inducing vaccines for optimal protection of the individual and inhibition of inter-individual transmission (herd immunity), while at the same time explain why induction of a strong systemic T-cell response may still impact viral transmission.